Effect of Menopause on Low Density Lipoprotein - Khanam, Shafeya; Reaz, Nahid; Jahan, Shahnaj Akter; Md Asaduzzaman, Mirza; Purabi, Ayesha Siddika; Hoque, Naima Sharmin (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: The present study was done on postmenopausal and premenopausal women with an objective to evaluate the effect of menopause on LDL cholesterol. Patients & Methods: The cross-sectional analytical study was done in the Departments of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka over a period 1 year between July 2012 to June 2013. A total of 60 women who underwent natural menopause were consecutively included in the study as case, while an equal number of premenopausal women were included as control. The outcome variable was level of serum LDL cholesterol. Result: The study demonstrated that 60% of postmenopausal women were > 50years old with mean age being 51.2 ± 2.7 years, whereas 40% of premenopausal women were in their 4th decades life with mean age being 39.1 ± 8.1 years (p = 0.001). There was no significant difference between the groups in terms of BMI with mean BMI of the former and the later groups being 24.45 ± 3.43 and 23.76 ± 3.46 kg/m2. The mean serum cholesterol was observed to be significantly higher in case group than that in the control group (212.3 ± 50.1 vs. 186.3 ± 38.2 mg/dl, p = 0.002). The LDL cholesterol was also significantly higher in the case group than that in the control group (141.47 ± 47.9 vs. 124.2 ± 31.5 mg/dl, p < 0.001). However, the groups were almost homogeneous with respect to HDL cholesterol and triglycerides (38.2 ± 5.0 vs. 37.6 ± 5.3 mg/dl, p =0.526 and 167.0 ± 67.2 vs. 181.0 ± 82.6 3 mg/dl, p = 0.311 respectively). Nearly three-quarters (73.3%) of the cases exhibited elevated serum LDL cholesterol compared to one-third (33.3%) of the controls. The risk of having raised LDL in case is more than 5(95% CI = 2.5 – 12.1) times higher than that in controls. The correlation graph between duration of menopause and serum LDL level showed that the two variables bear linear relationship (r = +0.338, p = 0.008). Conclusion: The postmenopausal women are at increased risk of having higher LDL cholesterol than the premenopausal women and longer the duration of menopause the higher the level of LDL Cholesterol. Ibrahim Cardiac Med J 2014; 4(2): 32-36